2009
DOI: 10.1002/lary.20759
|View full text |Cite
|
Sign up to set email alerts
|

AM‐111 prevents hearing loss from semicircular canal injury in otitis media

Abstract: Objectives/Hypothesis:Iatrogenic semicircular canal (SC) transection during mastoidectomy for chronic otitis media often leads to profound hearing loss. AM‐111, an apoptosis inhibitor, has been shown to mitigate hearing loss resulting from a variety of inner ear injuries. The goal of this study was to determine if round window application of AM‐111 following SC transection in the presence of Pseudomonas aeruginosa otitis media (PA‐OM) may reduce the associated hearing loss.Study Design:Prospective, randomized,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…It is now distributed for clinical and experimental studies by Auris Medical (Switzerland). The compound was effective in animal experiments in preventing neomycin ototoxicity and hearing loss due to acoustic trauma (14,15), semicircular canal injury (21), and acute labyrinthitis (16). In a study of focal cerebral ischemia, the active substance also was effective in the reduction of early calpain activation, late caspase 3 activation, and autophagosome formation, indicating involvement of the JNK pathway in 3 different types of cell death: necrosis, apoptosis, and autophagic cell death.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It is now distributed for clinical and experimental studies by Auris Medical (Switzerland). The compound was effective in animal experiments in preventing neomycin ototoxicity and hearing loss due to acoustic trauma (14,15), semicircular canal injury (21), and acute labyrinthitis (16). In a study of focal cerebral ischemia, the active substance also was effective in the reduction of early calpain activation, late caspase 3 activation, and autophagosome formation, indicating involvement of the JNK pathway in 3 different types of cell death: necrosis, apoptosis, and autophagic cell death.…”
Section: Discussionmentioning
confidence: 96%
“…It also possessed long pharmacologic activity due to a highly protease-resistant D-retro-inverso form (11). AM-111 has been shown to be effective in protecting hearing in the presence of various cochlear insults, such as noise trauma (11Y15), acute labyrinthitis (16), cochlear implant electrode insertion trauma (17Y19), aminoglycoside ototoxicity (11,18,20), and semicircular canal injury in otitis media (21). However, its effects on ischemic cochlear damage remain unclear.…”
mentioning
confidence: 99%
“…37,4244 AM-111 has also been shown to protect against hearing loss in cases of semicircular canal transection in a guinea pig otitis media model. 45 AM-111 is administered topically in a biodegradable gel scaffold that is applied at the round-window membrane. Reported benefits of this delivery method include potential for intraoperative application and ease of trans-tympanic injection.…”
Section: Discussionmentioning
confidence: 99%
“…More recent preclinical data suggests that peptide inhibitor treatment in the 5xFAD model improves cognitive performance and decreases amyloid load, mirroring the effect of genetic deletion of JNK3 (Gourmaud et al, 2018). In addition, several preclinical studies revealed a protective effect of the peptide inhibitors in hearing loss following acoustic trauma; this led to subsequent clinical development for acoustic trauma and acute sensorineural hearing loss resulting in statistically significant positive effects (Grindal et al, 2010;Omotehara et al, 2011;Suckfuell et al, 2014;Eshraghi et al, 2018).…”
Section: Biological Rationalementioning
confidence: 97%